2021
DOI: 10.1177/1745691620968771
|View full text |Cite
|
Sign up to set email alerts
|

The Empirical Status of Mindfulness-Based Interventions: A Systematic Review of 44 Meta-Analyses of Randomized Controlled Trials

Abstract: In response to questions regarding the scientific basis for mindfulness-based interventions (MBIs), we evaluated their empirical status by systematically reviewing meta-analyses of randomized controlled trials (RCTs). We searched six databases for effect sizes based on four or more trials that did not combine passive and active controls. Heterogeneity, moderators, tests of publication bias, risk of bias, and adverse effects were also extracted. Representative effect sizes based on the largest number of studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
191
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(205 citation statements)
references
References 97 publications
10
191
0
4
Order By: Relevance
“…Mindfulness constitutes a mental training in which individuals learn to train their attention in order to gain a greater awareness of one's thoughts, emotions, bodily sensations, and behaviors. This enhanced awareness may strengthen the self-regulation skills needed to effectively cope with life challenges and develop a deeper sense of well-being (González-García et al, 2016). These mechanisms are of particular interest in the face of the COVID-19 pandemic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness constitutes a mental training in which individuals learn to train their attention in order to gain a greater awareness of one's thoughts, emotions, bodily sensations, and behaviors. This enhanced awareness may strengthen the self-regulation skills needed to effectively cope with life challenges and develop a deeper sense of well-being (González-García et al, 2016). These mechanisms are of particular interest in the face of the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…There is compelling evidence on the effectiveness of MBIs in reducing stress and promoting mental health both in the general population and in a wide range of clinical populations (Chiesa & Serretti, 2011;Goldberg et al, 2021;Khoury et al, 2015). Several review studies have shown that MBIs can promote mental health and psychological well-being in undergraduate students (Chiodelli et al, 2020;Halladay et al, 2019;McConville et al, 2017).…”
mentioning
confidence: 99%
“…This first explorative implementation employed a randomized pre-post design with two different intervention groups. However, this approach does not meet the gold standard of randomized control trials in intervention research (e.g., Lupşa et al, 2020;Goldberg et al, 2021). With regards to the sample size and the pandemic situation we did not include a control group without a resilience intervention.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…One such approach that has a proven track record of providing psychophysiological benefits is mindfulness (e.g., An et al, 2019 ; Goldberg et al, 2021 ; Khoury et al, 2013 ; Pascoe et al, 2021 ). Mindfulness has proven to be efficacious not only in times of crisis, but also in alleviating a range of mental and physical ailments in a variety of other contexts.…”
Section: Mindfulness Practice During Covid-19 Crisis: Implications For Confinement Physical Inactivity and Sedentarismmentioning
confidence: 99%